A multisided C2 B-spline patch over extraordinary vertices in quadrilateral meshes. (October 2020) - Hettinga, Gerben J.; Kosinka, Jiří
Abstract: We propose a generalised B-spline construction that extends uniform bicubic B-splines to multisided regions spanned over extraordinary vertices in quadrilateral meshes. We show how the structure of the generalised Bézier patch introduced by Várady et al. can be adjusted to work with B-spline basis functions. We create ribbon surfaces based on B-splines using special basis functions. The resulting multisided surfaces are C 2 continuous internally and connect with G 2 continuity to adjacent regular and other multisided B-splines patches. We visually assess the quality of these surfaces and compare them to Catmull–Clark limit surfaces on several challenging geometrical configurations. Graphical abstract: Highlights: We present a generalised B-spline construction over extraordinary vertices. We construct B-spline ribbons with special basis functions. Our C 2 patches join with G 2 continuity to regular B-spline regions